The Complexity of Dreams: A Proposal on Its Use in Psychotherapeutic Practice - Giorgio Caviglia (Advancement and New Understanding in Medical Science Vol. 6, 2024)
With respect to psychoanalysis and clinical cognitivism, analysing the literature in this regard, I would say that the theoretical interest and clinical use of dreams is vivid, but depends very much on the specific model that is followed. My contribution to the discussion includes the statement that the use of dreams is still relevant in the clinical practice of psychotherapists of different orientations.